KOMPETENSI PEDAGOGIK GURU DALAM PEMBELAJARAN LURING DI SDN 4 SINDUE TOMBUSABORA - Azizah Thalib; Siska Ananda (COLLASE (Creative of Learning Students Elementary Education), 2023)
The formulation of the problem in this research is how is the teacher's pedagogic competency in offline learning and what are the obstacles faced by the teacher in the pedagogical domain during the offline learning period at SDN 4 Sindue Tombusabora. The teacher's pedagogic competence in offline learning is 1) to find out the teacher's pedagogic competence during the offline learning period and 2) to find out what are the obstacles faced by the teacher in the pedagogic domain during the offline learning. The type of research used is descriptive qualitative. The collection of data used is observation, interviews, documentation and questionnaires. The results of this study are 1) Ability to manage offline learning, 2) Teacher's understanding of students 3) Curriculum/syllabus development is adapted to the conditions and situation of the Covid-19 period. 4) Learning design is adapted to the psychological needs of students when participating in offline learning. 5) The implementation of educational learning is carried out in order to build communication between teachers and students. 6) Utilization of learning technology or educational facilities in the form of books or sober learning media and others. 7) Evaluation of learning to find out changes in behavior and character formation of students through material that has been previously studied. 8) The teacher gives the opportunity to develop the potential of students such as singing, drawing and students who are active in asking questions. Obstacles in carrying out offline learning during the Covid-19 period include the lack of motivation and concentration of students so that students get bored due to the lack of time the teacher has in the learning process.